A novel cetyltrimethylammonium bromide-based deep eutectic solvent pretreatment of rice husk to efficiently enhance its enzymatic hydrolysis. (May 2023) - Tang, Zhengyu; Wu, Changqing; Tang, Wei; Ma, Cuiluan; He, Yu-Cai
Graphical abstract: Highlights: Surfactant CTAB and lactic acid (LA) were used to prepare deep eutectic solvent. CTAB:LA effectively removed lignin (51.5%) and xylan (79.9%) in rice husk (RH). The enzymatic hydrolysis activity of CTAB:LA-treated RH was 5 times than that of RH. An increased accessibility and dropped hydrophobicity were observed on the treated RH. The enhanced enzymatic hydrolysis was interpreted by a series of characterizations. Abstract: Deep eutectic solvent (DES) has caught widely attention of researchers in biomass pretreatment. As a highly efficient surfactant, cetyltrimethylammonium bromide (CTAB) was expected to be used for synthesizing new DESs with additional functions in pretreatment. In this work, an efficient pretreatment method using a mixture of CTAB and lactic acid (LA) as a novel functional DES was established to improve enzymatic digestion efficiency of rice husk (RH). The results showed that DES CTAB:LA effectively removed lignin (51.5%) and xylan (79.9%) and the enzymatic hydrolysis activity of CTAB:LA-treated RH was 5 times that of RH. Then, a series of characterization demonstrated that a substantial accessibility increased, a hydrophobicity and lignin surface area decreased, and great surface morphology alternation were observed on the treated RH, which explained the increase in enzymatic hydrolysis efficiency. Overall, the discovery of more functional DESs might be motivated and biorefinery pretreatment processes might be greatly promoted.